SOSIALISASI PEMBERDAYAAN KADER POSYANDU DI PUSKESMAS TANJUNG MORAWA - Marice Simarmata; Ika Nur Saputri; Raisha Octavariny; Delita Br Panjaitan; Irmayani Irmayani; Irma Nurianti (JURNAL PENGMAS KESTRA (JPK), 2021)
Stunting in infants and toddlers is a chronic nutritional problem that requires comprehensive management and involves various cross-sectors. In 2018, it was determined that stunting management was a national development priority through the National Action Plan for Nutrition and Food Security in Indonesia. Tanjang Morawa District is one of the cases where there are cases of stunting. Stunting management efforts by optimizing conditions in the first 1000 days of life (HPK) can be implemented at Posyandu. Posyandu as a form of community empowerment in the health sector has a strategic role, however, because posyandu cadres have a diverse educational and socio-cultural background, their knowledge and skills need to be continuously updated. In the case of stunting, various studies have shown that the knowledge and skills of cadres related to stunting and prevention efforts are mostly not good, therefore efforts to increase the capacity of posyandu cadres are important. The training activities for 20 posyandu cadres were carried out in three stages, namely program socialization, training preparation and implementation, using a deductive model approach, training materials were compiled based on field observation data which was then discussed with expert sources. After training posyandu cadres can better understand balanced nutrition, early detection of stunting and the important role of posyandu cadres to inform optimal nutrition at 1000 HPK as an effort to prevent stunting and identify risk factors for stunting in the posyandu working area. It is known from the increase in the results of knowledge on the test after training. It is hoped that this capacity building will be made as continuous training that is periodic and well programmed